Editorial - Farooqi, A A (Cellular and Molecular Biology, 2016)
To optimize treatment, we need to understand biology of different diseases in much more detail with emphasis on morphological, proteomic, genetic and epigenetic grounds. Keeping in view the facts and stimulating developments in molecular pathology, it is worthwhile to present an up-date on this topic.It is becoming progressively more understandable that exciting fields of pharmacogenomics and pharmacogenetics have revolutionized field of medicine. Better understanding of underlying mechanisms of different diseases has provided us with better ways to treat illnesses. There cannot be a distinct definition of ’discipline’ of pathology, mainly because investigation of human disease encompasses all the scientific disciplines of biomedical research. Sen et al reported that hyperbarÄ±c oxygen (HBO) administration affected the endocrinological functions of fat tissue. Observation of significant increases in leptin, visfatin and IL-10 levels, leads to the consideration that in near future HBO administration may be applied as treatment for obesity, DM, eating disorders and obesity related diseases...